Pelayanan Administrasi Penerbitan Surat Keterangan Keberadaan Organisasi Kemasyarakatan /LSM pada Badan Kesatuan Bangsa dan Politik Pemprov Jatim - Pristi Wahyudi; Dandy Patria W; Sapto Pramono (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the challenges and solutions in bureaucratic transformation towards digitalization in government institutions, with a focus on the administrative services for issuing Certificates of Existence of Mass Organizations/NGOs by the National Unity and Politics Agency (Kesbangpol). The main obstacles identified include data fragmentation, outdated regulations, rigid organizational structures, and resistance to change. Limited human resource competency and political instability also hamper the implementation of reforms. To address these challenges, it is crucial to develop a comprehensive reform roadmap, simplify regulations, and strengthen data integration. Cybersecurity infrastructure development, organizational restructuring, and human resource capacity building through digital training are essential. Furthermore, strong political commitment is crucial to ensure the sustainability of reforms. Interviews indicate that service quality, verification standards, and speed of service influence public trust and satisfaction. Successful bureaucratic reform requires a combination of technological, regulatory, organizational, and cultural strategies to create modern and responsive public services.